Antistress/Adaptogenic Activity ofBauhinia variegata Against Different Stress Paradigms - Anil Reddy, M (International Journal of Pharmaceutical & Biological Archive, 2014)
Antistress/Adaptogenic Activity ofBauhinia variegata Against Different Stress Paradigms